THE ROLE OF REQUIREMENTS IN TALENT MANAGEMENT AND STRATEGIES FOR OVERALL HUMAN DEVELOPMENT - 1. Dr. Abhijaat Sahu, 2. Joymalya Bhattacharya (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This research paper delves into the critical role of requirements in talent management and their implications for holistic human development within organizations. It emphasizes the necessity of well-defined criteria for attracting, nurturing, and retaining talent, which align with strategic organizational goals. The paper outlines the influence of these requirements on key talent management functions, including recruitment, training, performance evaluation, and retention, while advocating for a comprehensive approach that prioritizes emotional health, work-life balance, and ethical principles. By presenting strategic frameworks for workforce planning, learning and development, performance management, and employee engagement, the study illustrates how organizations can cultivate a motivated workforce that enhances innovation and productivity. Additionally, it highlights case studies of successful implementations, demonstrating that cohesive talent management strategies can lead to improved employee engagement, retention, and overall organizational performance. Lastly, the paper anticipates future trends in talent management, advocating for adaptable role specifications, personalized alignment of roles, and a focus on soft skills, thereby underscoring the evolving nature of talent management in response to technological and societal changes.